2020
DOI: 10.3390/cancers12040926
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Responses in Hepatocellular Carcinoma: Implications for Novel Immunotherapeutic Approaches

Abstract: Hepatocellular carcinoma (HCC) still represents a significant complication of chronic liver disease, particularly when cirrhosis ensues. Current treatment options include surgery, loco-regional procedures and chemotherapy, according to specific clinical practice guidelines. Immunotherapy with check-point inhibitors, aimed at rescuing T-cells from exhaustion, has been applied as second-line therapy with limited and variable success. Natural killer (NK) cells are an essential component of innate immunity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 105 publications
(112 reference statements)
0
34
0
Order By: Relevance
“…Indeed, preclinical studies have found that NK cells and T cells are able to kill HCC tumor cells in vitro, and there are many factors in HCC microenvironments contribute to reduced intratumoral NK cell function. [41][42][43] We found that high-risk HCC patients exhibited significantly reduced NK cell infiltration relative to low-risk patients (P ¼ 0.002). This reduced NK cell infiltration likely contributes to the immune evasion and progression of this cancer type, potentially explaining the differences in survival outcomes between these 2 risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, preclinical studies have found that NK cells and T cells are able to kill HCC tumor cells in vitro, and there are many factors in HCC microenvironments contribute to reduced intratumoral NK cell function. [41][42][43] We found that high-risk HCC patients exhibited significantly reduced NK cell infiltration relative to low-risk patients (P ¼ 0.002). This reduced NK cell infiltration likely contributes to the immune evasion and progression of this cancer type, potentially explaining the differences in survival outcomes between these 2 risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although some progress is also being made to apply NK cell-based therapies against solid tumors, response rates in patients remain to be unsatisfied 163 . In HCC, several NK-cell based I/II phase clinical trials are in progress, such as, autologous/allogeneic NK cells infusion or in combination with other therapies (NCT03319459, NCT04162158, NCT03592706), anti-MUC1 CAR-NK cells (NCT02839954), and so on 168 . Moreover, related studies have showed that chemotherapy or radiation therapy can increase the amounts of CSCs in various tumor and induce up-regulating NKG2D ligands MICA and MICB on CSCs, indicating that NK cell-based immunotherapies in combination with radiation therapy or chemotherapy could better eradicate CSCs in HCC 169 .…”
Section: External Mechanisms Of Immune Evasionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide with a high mortality rate (Du et al, 2016;Nie et al, 2018). Immune escape is emerging as important contributors to the pathogenesis of HCC through remodeling the tumor microenvironment (Liu et al, 2018a;Mantovani et al, 2020). Aberrant overexpression of programmed death-ligand-1 (PD-L1) has been observed in hepatocellular carcinoma cells (Zhong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%